2017
DOI: 10.1590/0102-33062016abb0407
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of arsenic-contaminated water: the role of antioxidant metabolism of Azolla caroliniana Willd. (Salviniales)

Abstract: Phytoremediation has proven to be an effi cient technology for removing arsenic (As) from water, but the plants used in this process need to be tolerant to the damage caused by As. Th e toxic eff ect of As on growth and functioning of the antioxidant system was studied in individual plants of Azolla caroliniana exposed to fi ve concentrations of As (0.0, 0.25, 0.5, 1.0 and 1.5 mg L -1 ) for the course of fi ve days. Growth, As absorption, enzymatic activity, total and non-protein thiols and anthocyanin content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It is possible that even the high levels of ROS present in plants treated with As ? SNP compared with control plants were not enough to induce oxidative damage, yet similar levels of ROS have been previous demonstrated to induce oxidative stress in other aquatic plant species (Farnese et al 2014a;Leão et al 2017). Considering that the ROS levels measured in As ?…”
Section: Treatmentsmentioning
confidence: 49%
“…It is possible that even the high levels of ROS present in plants treated with As ? SNP compared with control plants were not enough to induce oxidative damage, yet similar levels of ROS have been previous demonstrated to induce oxidative stress in other aquatic plant species (Farnese et al 2014a;Leão et al 2017). Considering that the ROS levels measured in As ?…”
Section: Treatmentsmentioning
confidence: 49%
“…While Azolla filiculoides Lam is able to tolerate up to 4 mg L -1 hidrazin as well as Cd, Cr, Cu, Ni, and Zn at 10 000 mg L -1 , 1 990 mg L -1 , 9 000 mg L -1 , and 650 mg L -1 , consecutively [24,25], Azolla caroliniana Lam. is adept in absorbing pollutant up to the concentration of As 386.1 g g -1 dry weight [26] and Azolla pinnata R.Br. is capable of degrading pollutant in contaminated river water [27].…”
Section: Azolla For Water Phytoremediationmentioning
confidence: 99%
“…Although a limited negative effect of toxic elements was observed on biomass production, a high decrease in Cd percentage (to around 22%) and less reduction in Pb (to around 90%) in wastewaters were noted. Wild A. caroliniana was assessed for its removal potential of arsenic (As) from polluted water [17]. Authors found a high tolerance of this species for As associated with a considerable removal of this toxic element from water.…”
Section: Compostmentioning
confidence: 99%
“…Horticulturae 2022, 8, x FOR PEER REVIEW 3 of 13 [17]. Authors found a high tolerance of this species for As associated with a considerable removal of this toxic element from water.…”
Section: Introductionmentioning
confidence: 99%